Pendampingan Tata Kelola dan Pertanggungjawaban Keuangan Unit Usaha Bumdes Pulotondo - Dyah Metha Nurfitriasih; Retno Widiastuti; Ari Kamayanti; Padma Adriana Sari; Sri Hudiarini; Galuh Kartiko (Indonesian Journal Publisher, 2025)
BUMDes Pulotondo is a strategic partner of the village government in promoting development and economic equality at the local level. As a village financial institution, BUMDes plays an important role in supporting the needs of micro enterprises in the village. However, the financial management of BUMDes Pulotondo is still conducted in a simple manner. Financial management is limited to basic cash recording, while financial reporting is still lacking in detail and does not meet adequate accountability principles. In addition, there is no separate financial accountability report for each business unit, which leads to low transparency and difficulties in evaluating the performance of each BUMDes Pulotondo business unit. This study aims to analyze the financial management of BUMDes Pulotondo and identify solutions to improve the effectiveness and transparency of its financial management. To address this issue, the PPM Accounting Team of Polinema provided direct assistance to the management of BUMDes Pulotondo in improving financial governance. The assistance was carried out through the delivery of materials using interactive presentations, along with practical exercises for preparing financial reports using templates in Excel customized to meet the needs of BUMDes. Direct practice involved providing case studies of real transactions relevant to the activities of BUMDes for practicing financial report preparation. During the practical sessions, the management of BUMDes Pulotondo was enthusiastic about trying to identify transactions of business units present in Pulotondo Village and posed questions that they still did not understand regarding accounting. The PPM Team also created a guidebook and educational videos as ongoing references for the management of BUMDes Pulotondo in preparing financial reports accurately and systematically. The results of the BUMDes mentoring activities, BUMDes managers gave a positive response, namely the ease in understanding and preparing financial reports for business units in Pulotondo Village